Compact SnO2/Mesoporous TiO2 Bilayer Electron Transport Layer for Perovskite Solar Cells Fabricated at Low Process Temperature - Junyeong Lee; Jongbok Kim; Chang-Su Kim; Sungjin Jo (Nanomaterials, 2022)
Charge transport layers have been found to be crucial for high-performance perovskite solar cells (PSCs). SnO2 has been extensively investigated as an alternative material for the traditional TiO2 electron transport layer (ETL). The challenges facing the successful application of SnO2 ETLs are degradation during the high-temperature process and voltage loss due to the lower conduction band. To achieve highly efficient PSCs using a SnO2 ETL, low-temperature-processed mesoporous TiO2 (LT m-TiO2) was combined with compact SnO2 to construct a bilayer ETL. The use of LT m-TiO2 can prevent the degradation of SnO2 as well as enlarge the interfacial contacts between the light-absorbing layer and the ETL. SnO2/TiO2 bilayer-based PSCs showed much higher power conversion efficiency than single SnO2 ETL-based PSCs.